2006
DOI: 10.4049/jimmunol.176.11.6647
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced IL-1β Production by Human Uterine Macrophages Up-Regulates Uterine Epithelial Cell Expression of Human β-Defensin 2

Abstract: The uterine endometrium coordinates a wide spectrum of physiologic and immunologic functions, including endometrial receptivity and implantation as well as defense against sexually transmitted pathogens. Macrophages and epithelial cells cooperatively mediate innate host defense against bacterial invasion through the generation of immunologic effectors, including cytokines and antimicrobial peptides. In this study, we demonstrate that stimulation of peripheral blood monocytes and uterine macrophages with bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 60 publications
3
66
0
2
Order By: Relevance
“…In addition to several cytokines, the present studies indicated that the hBD-2 and NGAL genes are targets for IκB-ζ -mediated transcription. Consistent with the induction spectrum of IκB-ζ , both the hBD-2 and NGAL genes are induced preferentially by IL-1β, but not by TNF-α in A549 human lung adenocarcinoma cells, keratinocytes and other cells [25][26][27][28][29][30]. A recent report has also shown critical roles for IκB-ζ in IL-1β-dependent induction of the genes [38].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In addition to several cytokines, the present studies indicated that the hBD-2 and NGAL genes are targets for IκB-ζ -mediated transcription. Consistent with the induction spectrum of IκB-ζ , both the hBD-2 and NGAL genes are induced preferentially by IL-1β, but not by TNF-α in A549 human lung adenocarcinoma cells, keratinocytes and other cells [25][26][27][28][29][30]. A recent report has also shown critical roles for IκB-ζ in IL-1β-dependent induction of the genes [38].…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, we analysed the molecular mechanisms of the IκB-ζ -mediated transcriptional activation. We focused on hBD-2 (human β-defensin 2) and NGAL (neutrophil gelatinase-associated lipocalin), both of which are preferentially induced by stimulators of TLR/IL-1 receptor signalling pathways, rather than by TNF-α [25][26][27][28][29][30]. We found that the promoters of both genes are synergistically activated by co-transfection of IκB-ζ and NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1R autocrine signaling has not been investigated downstream of other PRRs, with the exception of TLR4 (5-7) and TLR9 (5,6,8,9), to our knowledge. Given the dramatic contribution of autocrine IL-1␤ to Nod2 responses, we examined whether the loop contributes to cytokine secretion by multiple PRR.…”
Section: Il-1r Autocrine Signaling Contributes To Cytokine Induction mentioning
confidence: 99%
“…MDP treatment activates NF-B and MAPK pathways and induces cytokines, including IL-1␤, in multiple human and mouse cell populations, including myeloid-derived cells (1)(2)(3)(4). Autocrine IL-1␤ is implicated in amplifying Tolllike receptor (TLR) cytokine induction, in particular by TLR4 (5-7) and TLR9 (5,6,8,9), however, the mechanism of this contribution is not well understood. The few reports addressing the IL-1␤ autocrine loop in Nod2 signaling have yielded mixed results.…”
mentioning
confidence: 99%
“…In chorionic explants MIF secretion is dose-dependently modulated by 17 -estradiol (E2) . As for progesterone, it favours the secretion of IL-3, IL-4, IL-5 and IL-10, that are reported to inhibit the Th1 response (Pioli et al, 2006). Interestingly, however, dydrogesterone induction of a Th1 to Th2 cytokine shift is also expressed by inhibition of IFN-and TNF-but up-regulation of the production of IL-4 and IL-6.…”
Section: Lifmentioning
confidence: 89%